Study of levofloxacin electrochemical sensors on screen-printed carbon electrodes - Putri, Ilmanda Zalzabhila Danistya; Jiwanti, Prastika Krisma; Romadhon, Achmad Badrus Zaman Rifky (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Levofloxacin (LEV) is a type of fluoroquinolone antibiotic that usually used for treating the bacterial infection. The released of LEV in environment may impact a significant risk to the ecosystems. Thus, a fast and sensitive sensor device is required. In this work, the detection of LEV is carried out using a screen-printed carbon electrode (SPE). The measurement methods used were square wave voltammetry and cyclic voltammetry. The limit of detection and limit quantitation were 4.34 µM, 14.4 µM, respectively. The relative standard deviation was obtained at 5.4%. The %recovery results obtained using screen printed electrode in drug, milk, and wastewater were in the range of 95-110%. The validated method was successfully applied to detect the levofloxacin and resulted in a sensitive and efficient measurement.